Pengaruh Model Pembelajaran Differentiated Science Inquiry (DSI) terhadap Hasil Belajar Peserta Didik Kelas VII SMP Negeri 6 Makassar - Nadia Mumtaz Hairuddin; Sitti Rahma Yunus; Ramlawati Ramlawati (Universitas Negeri Makassar, 2024)
This research aims to find out: 1) The level of learning outcomes of students in class VIII SMP Negeri 6 Makassar before and after being taught using the DSI model on vibration, wave and sound material 2) The level of learning outcomes of students of grade VIII SMP Negeri 6 Makassar before and after being taught using the Structured Inquiry model on vibration, wave and sound material 3) The increase in learning outcomes of VIII grade students of SMP Negeri 6 Makassar after being taught using the DSI model on vibration, wave and sound material 4) The effect of using the DSI model on the learning outcomes of VIII grade students of SMP Negeri 6 Makassar on the material of vibrations, waves and sound. This type of research is Quasi Experiment research with a research design using Nonequivalent Control Group Design. The population is all students of class VIII SMP Negeri 6 Makassar consisting of 11 classes with a total of 373 students. Samples were selected by Purposive Sampling, with 2 classes, namely class VIII.A as an experimental class totaling 26 people and class VIII.E totaling 27 people as a control class. The research instrument is in the form of a test question on student learning outcomes. Data collection was done by giving Pretest and Posttest. The data were analyzed by descriptive statistical analysis and inferential statistical analysis so that it was found that: 1) The level of learning outcomes of students before being taught with the DSI model is in the low category. While the category of student learning outcomes after being taught with the DSI model is in the high category with an average score of 14.3. 2) The level of student learning outcomes before being taught with the Structured Inquiry model is in the low category. While the category of student learning outcomes after being taught with the Structured Inquiry model is in the high category with an average score of 13.3.